DFT Investigation of Ligand Photodissociation in [Ru(II)(tpy)(bpy)(py)](2+) and [Ru(II)(tpy)(Me(2)bpy)(py)](2+) Complexes - Nisbett, Khalin (Inorg Chem, 2017)
Photoinduced ligand dissociation of pyridine occurs much more readily in [Ru(tpy)(Me(2)bpy)(py)](2+) than in [Ru(tpy)(bpy)(py)](2+) (tpy = 2,2′:6′,2″-terpyridine; bpy = 2,2′-bipyridine, Me(2)bpy = 6,6′-dimethyl-2,2′-bipyridine; py = pyridine). The S(0) ground state and the (3)MLCT and (3)MC excited states of these complexes have been studied using BP86 density functional theory with the SDD basis set and effective core potential on Ru and the 6–31G(d) basis set for the rest of the atoms. In both complexes, excitation by visible light and intersystem crossing leads to a (3)MLCT state in which an electron from a Ru d orbital has been promoted to a π* orbital of terpyridine, followed by pyridine release after internal conversion to a dissociative (3)MC state. Interaction between the methyl groups and the other ligands causes significantly more strain in [Ru(tpy)(Me(2)bpy)(py)](2+) than in [Ru(tpy)(bpy)(py)](2+), in both the S(0) and (3)MLCT states. Transition to the dissociative (3)MC states releases this strain, resulting in lower barriers for ligand dissociation from [Ru(tpy)(Me(2)bpy)(py)](2+) than from [Ru(tpy)(bpy)(py)](2+). Analysis of the molecular orbitals along relaxed scans for stretching the Ru–N bonds reveals that ligand photodissociation is promoted by orbital mixing between the ligand π* orbital of tpy in the (3)MLCT state and the dσ* orbitals that characterize the dissociative (3)MC states. Good overlap and strong mixing occur when the Ru–N bond of the leaving ligand is perpendicular to the π* orbital of terpyridine, favoring the release of pyridine positioned in a cis fashion to the terpyridine ligand.